Nanofiltration as pretreatment for seawater desalination - Truong, Vinh Hien (2019)
Seawater reverse osmosis (SWRO) has always been one of the favourite desalination technologies worldwide due to its high efficiency and low operating cost. However, one of the inherent drawbacks of SWRO is its prone to membrane fouling because of the high total dissolved solids concentration in seawater. As such, pre-treatment units have become more vital since they can effectively filter the seawater before the feed reaches the main reverse osmosis (RO) unit. Among the pre-treatment units, nanofiltration (NF) membrane has attracted more attention recently because with its nanoscale pores, NF can reject the divalent ions and in turn, reduces the scaling potential in RO membrane. In this project, the objective was to investigate the performance of the novel low-pressure hollow fibre NF membranes from Singapore Membrane Technology Centre in actual seawater conditions. The membranes, namely NF Loose (NFL) and NF Tight (NFT), were fabricated by the layer-by-layer deposition process and were compared with the commercial NF270 from Dow Filmtec, in terms of permeability, rejection, and the fouling potential on RO. At the pressure of 4 bars and 50% recovery, NFL had the highest flux of 10.6 L/m2.h (LMH) while NFT had the lowest flux of 5.30 LMH. As a trade-off for lower flux, under the same conditions, NFT achieved superior rejection properties for calcium (75.2%), magnesium (92.6%), and organic fraction that is heavier than 350 g/mol (more than 97%). Though NFL performance was not as good as NFT, both NFL and NFT, in general, surpassed NF270 in rejection properties. As a result, RO fouling potential, as indicated by the normalized flux at 50% recovery, reduced to a great extent when NFT and NFL permeate samples were used as feed, as compared to those of NF270 and ultrafiltration (UF) membranes. Due to its better balance between rejection and permeability, NFL was shown to be the preferred pre-treatment option, among the tested membranes, in SWRO desalination. With the results and information from this study, more experiments at a larger scale can be designed and conducted to better confirm the feasibility of applying these NF membranes in industrial context. This is so that the SWRO process can be more optimised and effective in delivering potable water to the people.